The Caribbean : from vulnerability to sustained growth - Sahay, Ratna; Robinson, David O.; Cashin, Paul.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This book sets out the economic challenges facing the island nations of the Caribbean and presents policy options to ameliorate external shocks and embark firmly on a sustained growth path.
Includes bibliographical references.
oif 17/09/15
Loan
Keywords: Caribbean Area -- Economic conditions; Fiscal policy -- Caribbean Area; Business cycles -- Caribbean Area; Natural disasters -- Economic aspects -- Caribbean Area; Tourism -- Caribbean Area; Brain drain -- Caribbean Area; Eastern Caribbean Currency Union